Impacts of Northern Pike on Stocked Rainbow Trout in Pactola Reservoir, South Dakota. (8th March 2016) - Scheibel, Natalie C.; Dembkowski, Daniel J.; Davis, Jacob L.; Chipps, Steven R.
Abstract: Establishment of nonnative Northern Pike Esox lucius in Pactola Reservoir, South Dakota, has prompted concern among biologists about the influence of this species on the lake's intensively managed salmonid fisheries. Ancedotal information suggests that catch rates of Rainbow Trout Oncorhynchus mykiss have declined while mean size and abundance of Northern Pike has increased, although quantitative information on diet and growth of the Northern Pike population is lacking. To address potential interactions between Northern Pike and Rainbow Trout, we assessed size‐dependent predation by Northern Pike on Rainbow Trout and determined the relative energetic contribution of stocked Rainbow Trout to Northern Pike growth using bioenergetics modeling. Stable isotopes combined with traditional diet analyses revealed that smaller Northern Pike (<600 mm TL) consumed primarily centrarchids and Rainbow Smelt Osmerus mordax, and Rainbow Trout contributed less than 10% to their annual energy consumption. In contrast, larger Northern Pike (≥600 mm TL) consumed primarily Rainbow Trout, which accounted for 56% of their annual energy consumption. Combining estimates of Northern Pike predation with production costs of catchable‐size Rainbow Trout revealed that annual economic losses ranged from US$15, 259 to $24, 801 per year. Over its lifespan, an age‐10 Northern Pike was estimated to consume ~117 Rainbow Trout worth approximately $340. Thus, Northern Pike predation substantially influences salmonid management initiatives and is likely a primary factor contributing to reduced Rainbow Trout abundance and return to anglers in Pactola Reservoir. Strategies for reducing Northern Pike predation on Rainbow Trout include increasing the size of stocked fish or altering the timing and spatial distribution of stocking events. Received June 5, 2015; accepted November 2, 2015 Published online March 8, 2016